Double Pump Sequential Constant Citrate Anticoagulation in General Hemodialysis - Li Tang; Jiali Zhang; Qijun Cheng; Jie Li; Ling Zhou; Li Wang; Changbin Liao (Applied Bionics and Biomechanics)
Objective. To investigate the safety and efficacy of single-pump and double-pump sequential anticoagulation in general hemodialysis under the condition of constant citrate. Methods. A total of 32 patients with end-stage renal disease complicated with hemorrhage admitted by Zigong Third People’s Hospital from December 2019 to December 2020 were collected. Randomly divided into single pump group (n=17) and double pump group (n=15). The coagulation of dialyzer and intravenous pot was compared between the two groups. Then, the changes of serum calcium before treatment, after 2 h treatment, and after the completion of the treatment, and the front of the blood pump and intravenous pot, as well as behind the intravenous pot were observed and recorded in the two groups. Then, single-pool clearance of urea/volume (spKt/V) was compared between the two groups. Results. There were few differences in dialyzer coagulation between the single pump group and double pump group. However, the single pump group had a significant increase in the number of intravenous pot coagulations than the double pump group. At 2 h for dialysis, the serum calcium level behind the intravenous pot in the double pump group was notably lower than that in the single pump group. And after the completion of dialysis, the serum calcium returned to pretreatment level. The Kt/v in both groups reached the normal standard without statistically significant difference. And there were no adverse reactions in the patients of both groups after dialysis. Conclusion. For hemodialysis patients with bleeding, dual-pump segmented anticoagulation is superior to single-pump anticoagulation in intravenous pot anticoagulation. Double pump segmented sequential constant citrate anticoagulation can be utilized as a new simple and effective anticoagulation method for clinical hemodialysis.